(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Paraquat poisoning is a highly lethal toxicological emergency associated with severe oxidative stress, systemic inflammation, and multi-organ failure. Despite various treatment strategies, mortality remains extremely high, and early prognostic indicators are essential for improving clinical decision-making. Methodology: This prospective observational study was conducted in the Department of Emergency Medicine, Sree Mookambika Institute of Medical Sciences, Kulasekharam, from June 2025 to March 2026. A total of 50 patients aged above 18 years with a history of paraquat poisoning were included. Patients with chronic liver disease, chronic kidney disease, malignancy, pulmonary disorders, connective tissue diseases, anemia, or history of steroid/antimetabolite use were excluded. Clinical evaluation and laboratory investigations including CBC, RFT, LFT, ESR, CRP, LDH, and ferritin were performed on day 1 and day 2. Statistical analysis was performed using chi-square test and independent t-test, with p < 0.05 considered significant. Results: The mean age of patients was 29.7 ± 7.8 years, with male predominance (86%). Mortality was 88% (n=44). Oral ulcers, acute kidney injury, and liver dysfunction were present in 98% of cases, while lung injury was observed in 88%. Non-survivors had significantly higher inflammatory markers compared to survivors: ESR (51.1 vs 24.7 mm/hr, p=0.01), CRP (36.8 vs 7 mg/L, p=0.04), LDH (461.1 vs 261.2 U/L, p=0.001), and ferritin (449.6 vs 233.2 ng/mL, p=0.001). Lung injury showed a strong association with mortality (p < 0.001). Conclusion: Paraquat poisoning is associated with extremely high mortality. Elevated acute inflammatory markers and pulmonary involvement are strongly associated with poor in-hospital outcomes. Early assessment of inflammatory biomarkers may aid in risk stratification and prognostication in paraquat poisoning.